2019
DOI: 10.2340/16501977-2548
|View full text |Cite
|
Sign up to set email alerts
|

Developing interventions to address sexuality after stroke: Findings from a four-panel modified Delphi study

Abstract: Although stroke often impacts on sexuality there are very limited programmes to provide sexual rehabilitation for stroke survivors or their partners. We asked stroke survivors, partners of stroke survivors, rehabilitation professionals and clinicians to identify what should be included in a sexual rehabilitation programme for stroke survivors, when this programme should be offered, what professionals should be involved in delivering the programme, and how they should provide the programme. The participants com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…support needs for hygiene or dressing). The Canadian Stroke Best Practice Recommendations suggest that sexuality be part of rehabilitation [5], especially in the subacute and chronic phases of recovery [6]. Considering the taboo related to sexuality [7], clinicians should initiate a conversation with stroke clients instead of waiting for them to raise the issue .…”
Section: Manuscript Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…support needs for hygiene or dressing). The Canadian Stroke Best Practice Recommendations suggest that sexuality be part of rehabilitation [5], especially in the subacute and chronic phases of recovery [6]. Considering the taboo related to sexuality [7], clinicians should initiate a conversation with stroke clients instead of waiting for them to raise the issue .…”
Section: Manuscript Introductionmentioning
confidence: 99%
“…written), few data were collected concerning the type of information that the clients sought. To our knowledge, only a study by McGrath and collaborators [6] has addressed this issue. Using a Delphi method, they interviewed persons who had sustained a stroke (n = 30), their partners (n = 18), and clinicians and researchers in stroke rehabilitation (n = 45) to prioritize core concepts to be considered in sexual counseling in stroke rehabilitation.…”
Section: Manuscript Introductionmentioning
confidence: 99%
“…Half of the participants in this study reported a high degree of problems with their sexual life. This problem has not been addressed previously among patients with TIA, although it is well-known among stroke survivors (30) with sexual rehabilitation needs (31). A cautious conclusion from the current study, due to limited sample size, is that this area needs further research and the problems should be addressed at follow-up with proper treatment and rehabilitation.…”
Section: Discussionmentioning
confidence: 76%
“…The PIADS can be a useful tool for evaluating this type of AT, but more exhaustive research is needed to inform clinicians of the best intervention strategies for use with this group [53], as well as ways of continuing these interventions in outpatient settings [71] using AT among other measures.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors such as McCluskey [52] show that one of the barriers to intervention in this group's sexual functioning is the lack of existing knowledge on the subject. There is no scientific evidence to justify the best intervention strategies for sexual functioning [53] or the use of AT among this group, although AT such as splints [54] is commonly used for mobility [13], including upper limb mobility [55]. However, no previous studies have used AT for sexual functioning as an intervention strategy.…”
Section: Introductionmentioning
confidence: 99%